The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0102-311x2010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes do estado de saúde de crianças ribeirinhas menores de dois anos de idade do Estado do Pará, Brasil: um estudo transversal

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
2
6
0
9
Order By: Relevance
“…However, prevalence in current study is consistent with other studies at different locations in Brazil (Chagas et al, 2013;Saavedra & Câmara, 2010;Silva & Moura, 2010;Silveira et al, 2010;Souza, Benício, Castro, Muniz, & Cardoso, 2012). The above indicated that there may be populations where acute malnutrition is significant from the point of view of public health.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, prevalence in current study is consistent with other studies at different locations in Brazil (Chagas et al, 2013;Saavedra & Câmara, 2010;Silva & Moura, 2010;Silveira et al, 2010;Souza, Benício, Castro, Muniz, & Cardoso, 2012). The above indicated that there may be populations where acute malnutrition is significant from the point of view of public health.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies on children from geographic contexts with predominant precarious living conditions also demonstrated greater prevalence of stunting when compared to rates in national surveys (PNDS and POF), as in São João do Tigre, in the semiarid region of the state of Paraiba (Oliveira et al, 2009) and Gameleira, in the Zona da Mata, state of Pernambuco (Oliveira et al, 2010), as well as among beneficiaries of the Family Allowance Program (Brasil, 2014), with rates for children under five years reaching 14.6, 16.5 and 12.2%, respectively. Similar results were also reported for children under two years in the rural settlements and camps in the Midwestern region in the state of Paraná (Lang, Almeida, & Taddei, 2011) and riverside communities in the state of Pará (Silva & Moura, 2010) as well as children under six years from the slum areas of Maceió, Alagoas (Silveira, Alves, Ferreira, Sawaya, & Florêncio, 2010) respectively with 8.0, 13.4 and 8.6%. It is relevant to note that data from under-two-year-old children may be directly compared to those of this study, since the population studied showed no anthropometric difference with regard to the child's age group.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Grande parte dos estudos realizados que consideraram a escolaridade materna como um possível indicador de desenvolvimento estabeleceu a correlação com outras variáveis sociodemográficas, tais como renda 24,25 , contexto em que vive (zona rural ou urbana) 23 , estrutura familiar 24,26 , linha de pobreza 24 , inserção dos pais no mercado de trabalho 26 e condições de moradia 26 …”
Section: Discussionunclassified
“…Contudo, em estudo com crianças em idade escolar a relação entre escolaridade materna e desenvolvimento neuropsicomotor não evidenciou significância estatística 21 . Estudos mostram que o contexto e o ambiente em que vive a criança podem influenciar o cuidado a que está exposta, as interações sociais e consequentemente, seu desenvolvimento [22][23][24][25][26] . A literatura revela ainda que mães com maior escolaridade tendem a valorizar mais a estimulação ofertada a criança 23 .…”
Section: Conclusãounclassified